2009
DOI: 10.1007/s00253-009-2135-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a bacterial cytochrome P450 for the metabolism of diclofenac

Abstract: The bacterium Actinoplanes sp. ATCC 53771 is known to perform drug metabolism of several xenobiotics similarly to humans. We identified a cytochrome P450 enzyme from this strain, CYP107E4, and expressed it in Escherichia coli using the pET101 vector. The purified enzyme showed the characteristic reduced-CO difference spectra with a peak at 450 nm, indicating the protein is produced in the active form with proper heme incorporation. The CYP107E4 enzyme was found to bind the drug diclofenac. Using redox enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 60 publications
0
21
1
6
Order By: Relevance
“…The CYP encoded by sare1259 is most closely related to rif-orf13 and rif-orf5 from the AM- rif cluster as well as other CYPs belonging to the CYP107 family. This superfamily includes a large number of bacterial CYPs, many of which are associated with xenobiotic degradation and secondary metabolite tailoring 29-32…”
Section: Discussionmentioning
confidence: 99%
“…The CYP encoded by sare1259 is most closely related to rif-orf13 and rif-orf5 from the AM- rif cluster as well as other CYPs belonging to the CYP107 family. This superfamily includes a large number of bacterial CYPs, many of which are associated with xenobiotic degradation and secondary metabolite tailoring 29-32…”
Section: Discussionmentioning
confidence: 99%
“…Studies with native enzymes originating from specialized or pure cultures help to reliably assign function to unknown proteins, thereby improving database annotations (Mills et al., 2015) and mechanistic understanding of degradation processes (Prior et al., 2009, Xu et al., 2015). However, pure or enriched laboratory cultures cannot provide reliable information about the diversity and activity of the enzymes actually involved in micropollutant degradation under environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2; Supplemental Table 2). These bacterial P450 enzymes are considered to be active drug metabolizers for several drugs including amitriptyline, chlorpromazine (2), and diclofenac (5) (Prior et al, 2010;Kulig et al, 2015). In addition, we have previously shown that CYP264A1 was able to convert tricyclic drug molecules (Litzenburger et al, 2015), and CYP265A1 and CYP266A1 were able to hydroxylate the antitumor drug epothilone D .…”
Section: Bioinformatics Studies and Comparison Of Cyp267a1 With Cyp267b1mentioning
confidence: 99%